Respuesta :
f(x) = x² - 8x + 5
x = -1
f(-1) = (-1)² - 8(-1) + 5
f(-1) = 1 - (-8) + 5
f(-1) = 1 + 8 + 5
f(-1) = 14
x = -1
f(-1) = (-1)² - 8(-1) + 5
f(-1) = 1 - (-8) + 5
f(-1) = 1 + 8 + 5
f(-1) = 14
The answer is: " 14 " .
_________________________________________________
Given: Let f(x) = x² − 8x + 5. Find f(−1).
f(−1) = (-1)² − 8(-1) + 5 = 1 − (-8) + 5 = 1 + 8 + 5 = 14.
_________________________________________________
_________________________________________________
Given: Let f(x) = x² − 8x + 5. Find f(−1).
f(−1) = (-1)² − 8(-1) + 5 = 1 − (-8) + 5 = 1 + 8 + 5 = 14.
_________________________________________________